The Main Problems of Scientific Support of Flax Growing - R. A. Rostovtsev; V. G. Chernikov; I. V. Ushchapovsky; R. A. Popov (Сельскохозяйственные машины и технологии)
Strategic plans for the economic development of the Russian Federation involve an increase in demand for natural fiber products, including linen, which will require an increase in the production of domestic linen in the near future. The authors examined the most important problems of scientific support for production increasing and the quality of flax products improving in the Russian Federation.(Research purpose) To assess the flax growing state and identify the problems of scientific support for improving the flax production quality.(Materials and methods) The authors studied the organizational aspects of fl ax cultivation and processing, new ways of harvesting crops, issues of technological processes mechanization and the state of farms’ technical equipment.(Results and discussion) The authors showed that the share of flax use in industrialized countries reached 24 percent in the textiles, paper, and composite materials production. They found out that the mechanization level at the flax mills did not exceed 40 percent. They presented a comparative analysis of the intensification level of Western European and domestic flax growing. They confirmed that separate cleaning technology could be applied on average at 25-30 percent of the harvested area, depending on weather conditions. It was determined that approximately 90 percent of treated plant fibres were received using a dewy lobe in Russia and abroad. The authors developed a new method of cleaning flax and a multifunctional unit for its implementation. During the experiments, they established a 50 percent increase in the productivity of new technical equipment, a 60 percent reduction in the heap content, and a 3-fold reduction in seed losses compared to harvesting with the LK-4A flax harvester. They showed the advantages of the method of the tape wrapping on linen, which created equal conditions for aging for the upper and lower layers, which was especially effective when the straw yield was more than 3.5 tons per hectare. Wrapping helped to increase the uniformity of straw in color in the upper and lower layers of the tape and increased the quality and quantity of flax seeds.(Conclusions) It was established that in order to increase the flax growing efficiency, a comprehensive modernization was necessary, which involved the solution of organizational, agronomic, technological and engineering issues.